Sacral Tumor: Experience in a Single Institution - KAMAL, ACHMAD FAUZI (Indonesian Journal of Cancer, 2015)
ABSTRACTIntroduction. Sacral tumors are rare, and experience of these tumors is usually limited to a small number of patients. Inthis study, we evaluated profile, survival rates, and functional outcome in a series of sacral tumor treated in our institution.Method. We retrospectively reviewed the records of 22 sacral tumor patients from January 1995 to February 2014 inCipto Mangunkusumo National Central Hospital, Jakarta, Indonesia. Kaplan-Meier method was used to describedsurvival and functional outcome. Their correlation with clinical profile, histological type, level of sacral involvement,treatment, and complication were analyzed by Log rank test.Results. From 22 patients, 5 of them were excluded from this study. Thus, there were 17 cases of sacral tumor, 16 ofthem were malignant and one case was benign. In Kaplan-Meier Analysis, there were no significant difference insurvival found between sex, age group, biopsy type, level of sacral involvement, treatment, and complication. There wassignificant difference in survival found between histopathology result (p=0.012), and giant cell tumor GCT showed thehighest survival, followed by chordoma, metastatic lession, and Ewing Sarcoma. Sacral tumor at the level of S2 andbelow had better functional outcome compared to the one above S2 (p=0.001). There were no difference in functionaloutcome found between histopathology type and treatment (p=0.137 and p=0.210).Conclusion. The majority of primary tumors of sacrum are chordoma which present with nonspecific early signs andsymptoms. Survival rate and functional outcome of the sacral tumor patients were determined by histopathology resultand level of sacral involvement. Lower level of sacral involvement lead to better survival and functional outcome.Keyword: sacral tumors, chordoma, giant-cell tumor, metastasis, survival, functional outcomeABSTRAKPendahuluan. Tumor sakrum sangat jarang ditemukan; dan pengalaman mengenai tumor sakrum biasanya terbataspada sejumlah kecil pasien. Dalam studi ini, kami mengevaluasi profil, tingkat kesintasan, dan luaran fungsional dariserangkaian tumor sakrum yang dirawat di institusi kami.Metode. Kami telah mengevaluasi 22 pasien tumor sakrum dari Januari 1995 sampai Februari 2014 secara retrospektif diRumah Sakit Umum Pusat Nasional Cipto Mangunkusumo Jakarta Indonesia. Metode Kaplan-Meier digunakan untukmenganalisis angka kesintasan dan luaran fungsional. Hubungan antara kesintasan dan luaran fungsional dengan profilklinis, jenis histopatologi, level sakrum yang terlibat, penatalaksanaan, dan komplikasi dianalisis dengan Log rank test.Hasil. Dari 22 pasien, hanya 17 pasien tumor sakrum yang dimasukkan ke dalam studi ini (5 kasus diekslusi), 16 kasusdengan tumor ganas dan 1 kasus dengan tumor jinak. Hasil analisis Kaplan-Meier menunjukkan tidak ada perbedaanyang bermakna pada angka kesintasan terhadap jenis kelamin, kelompok umur, jenis biopsi, level sakrum yang terlibat,penatalaksanaan, dan komplikasi. Hasil uji statististik menunjukkan perbedaan yang bermakna antara kesintasandengan hasil histopatologi (p = 0,012), giant cell tumor menunjukkan kesintasan hidup tertinggi, diikuti oleh Chordoma,lesi metastasis, dan Ewing Sarcoma. Tumor sakrum setinggi S2 ke bawah memiliki luaran fungsional yang lebih baikdibandingkan dengan level di atas S2 (p = 0,001). Hasil uji statistik menunjukkan tidak ada perbedaan yang bermakna antara luaran fungsional dengan jenis histopatologi dan penatalaksanaan(p = 0,137 dan p = 0,210). Kesimpulan. Mayoritas tumor primer pada tulang sakrum adalah chordoma yang muncul dengan gejala dan tanda-tanda awal yang tidak spesifik. Angka kesintasan dan luaran funsional pasien tumor sakrum dipengaruhi oleh jenis histopatologi dan level sacrum yang terlibat. Semakin rendah level sacrum yang terlibat, semakin baik kesintasan dan luaran fungsional.Kata Kunci: Tumor sakrum, Chordoma, giant cell tumor, metastasis,kesintasan, luaran fungsional